A cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time and a preparation method thereof
By using low-density polyethylene, crosslinking agent, accelerator, antioxidant and modified styrene-maleic anhydride copolymer in the crosslinking polyethylene insulating material, accelerator with heteronaphthalene biphenyl and benzimidazole structure, and accelerator with modified copolymers of multi-carbon nanotubes and erythritol, the problems of high by-product content, long degassing time and poor water tree resistance are solved, and a crosslinking polyethylene insulating material with ultra-short degassing time and excellent water tree resistance are achieved, which is suitable for high-voltage cables.
Patent Information
- Application Number
- CN202411078332.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-08-07
AI Technical Summary
The existing crosslinked polyethylene insulating materials have high by-product content during the crosslinking process, and the degassing time is too long, resulting in a decrease in the quality of the cable and a poor resistance to water tree, which affects the service life of high-voltage cables.
Low-density polyethylene is used as the main component, and crosslinking agent, aid crosslinking agent, antioxidant and modified styrene-maleic anhydride copolymer are added to prepare a crosslinking polyethylene insulating material for ultra-high voltage cables with ultra-short degassing time through synergistic action. The heteronaphthalene biphenyl structure and benzimidazole structure were introduced into the crosslinking agent, the modified styrene-maleic anhydride copolymer was grafted with multi-carbon nanotubes, and erythritol was introduced to improve the water tree resistance.
It realizes the ultra-short degassing time and excellent water tree resistance characteristics of crosslinked polyethylene insulating material, improves the quality and service life of the cable, and is suitable for the field of high-voltage cable insulating materials.
Smart Images

Figure BDA0004983000430000091 
Figure BDA0004983000430000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of cable insulation materials, and in particular to a cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time and a preparation method thereof. Background Art
[0002] Cross-linked polyethylene (XLPE) has the characteristics of high insulation resistance, low dielectric loss, resistance to solvent corrosion, resistance to aging, low price, easy availability, long life, excellent thermal stability, etc. It is widely used in the manufacturing of medium voltage, high voltage and ultra-high voltage wires and cables, and is currently the most important insulating material for wires and cables. The insulation principle of cross-linked polyethylene is to introduce a cross-linking agent into the polyethylene material and change the molecular structure of polyethylene through chemical or physical cross-linking reactions, thereby improving its insulation performance and mechanical strength. During the cross-linking reaction, a three-dimensional network structure is formed between the polyethylene molecular chains, which enhances its tensile strength, thermal stability and electrical properties.
[0003] At present, the commonly used cross-linked polyethylene insulation materials have the following two main defects. First, the by-product content of the insulation material is relatively high, which can easily cause scratches and insulation porosity problems on the cable surface. In particular, the degassing time of the cross-linked polyethylene is too long, and insufficient degassing leads to the production of small molecular precipitates, which causes the quality of the cable to decline and poses a safety hazard to the long-term operation of the high-voltage cable. Second, the cross-linked polyethylene has poor water tree resistance, which shortens the service life of the high-voltage cable.
[0004] Patent CN 116656026A discloses a water-tree-resistant cross-linked polyethylene cable material and a preparation method thereof. The raw materials of the cross-linked polyethylene cable material prepared in this application include polyethylene, modified SiO2 nanofiller, vinyl trimethoxysilane, cross-linking agent and antioxidant, and it has good mechanical properties, thermal stability and water-tree resistance, but it does not solve the problem of high by-product content and long degassing time in the cross-linking process of polyethylene; Patent CN 108623877A discloses an insulating material for high-voltage DC cable and a preparation method thereof. The insulating material prepared in this application includes polyethylene resin, antioxidant, cross-linking agent and auxiliary cross-linking agent. Compared with traditional cross-linked polyethylene insulating materials, this application adds auxiliary cross-linking agent, while maintaining the same cross-linking degree, the content of cross-linking agent is reduced. The degassing time of the cable is shortened and the insulation performance of the cable is improved, but this application does not solve the hidden danger that cross-linked polyethylene is prone to water treeing.
[0005] Therefore, there is an urgent need in the market for a cross-linked polyethylene insulation material for ultra-high voltage cables with good water tree resistance and ultra-short degassing time. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention selects low-density polyethylene as the main component, and then adds a cross-linking agent, a co-cross-linking agent, an antioxidant and a modified styrene-maleic anhydride copolymer to prepare a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time, which has an ultra-short degassing time and excellent anti-water treeing properties.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] On one hand, the present invention provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time. The cross-linked polyethylene insulation material comprises the following raw materials in parts by weight: 90-100 parts of low-density polyethylene, 1-2 parts of a cross-linking agent, 0.3-0.5 parts of a co-cross-linking agent, 2-6 parts of an antioxidant, and 4-10 parts of a modified styrene-maleic anhydride copolymer.
[0009] In some embodiments of the present invention, the density of the low-density polyethylene is 0.915-0.930 g / cm 3 .
[0010] In some embodiments of the present invention, the cross-linking agent is dicumyl peroxide.
[0011] In some embodiments of the present invention, the method for preparing the auxiliary cross-linking agent comprises the following steps:
[0012] (1) 4-(4-hydroxyphenyl)phthalazin-1-ol and p-chloronitrobenzene are mixed, heated to 135-145° C., potassium carbonate and DMF are added, and stirred to obtain product 1 for later use;
[0013] (2) adding Fe(NO3)3·9H2O to a monobutyric acid aqueous solution, stirring, adding aqueous ammonia to adjust the pH to 6-6.5, stirring, standing, centrifuging, washing, drying, adding dicyandiamide, grinding, introducing inert gas, heating to 500-600°C, keeping the temperature for 2-4 hours, then heating to 900-1000°C, keeping the temperature for 4-5 hours, cooling to room temperature, and obtaining a catalyst for use;
[0014] (3) taking the product 1 of step (1), adding the catalyst and hydrazine hydrate of step (2), stirring, and obtaining the product 2 for standby use;
[0015] (4) mixing the product 2 of step (3) and 2-(4-aminophenyl)-5-aminobenzimidazole, adding maleic anhydride and DMF, stirring, condensing and refluxing for 3-4 hours, filtering, washing, and drying to obtain the product 3 for use;
[0016] (5) The product 3 of step (4), triethylamine and acetone are mixed, an inert gas is introduced, the temperature is raised to 55-65° C., cobalt acetate and acetic anhydride are added, the mixture is stirred, filtered, washed and dried to obtain a cross-linking aid.
[0017] Wherein, in the step (3), the mass ratio of product 1 to catalyst is 1:(0.1-0.2).
[0018] Preferably, in step (3), the mass ratio of product 1 to catalyst is 1:0.15.
[0019] In some embodiments of the present invention, in step (1), the molar ratio of 4-(4-hydroxyphenyl)phthalazin-1-ol to p-chloronitrobenzene is 1:(2-2.1).
[0020] Preferably, in step (1), the molar ratio of 4-(4-hydroxyphenyl)phthalazin-1-ol to p-chloronitrobenzene is 1:2.
[0021] In some embodiments of the present invention, in step (4), the mass ratio of product 2 to 2-(4-aminophenyl)-5-aminobenzimidazole is 1:(0.7-0.9).
[0022] Preferably, in step (4), the mass ratio of product 2 to 2-(4-aminophenyl)-5-aminobenzimidazole is 1:0.8.
[0023] When preparing cross-linked polyethylene insulation materials, dicumyl peroxide cross-linking agents are often required. However, excessive use of cross-linking agents will lead to the production of some by-products and prolonged degassing time, resulting in a decrease in the quality of cross-linked polyethylene insulation materials. Therefore, reducing the amount of cross-linking agent and improving the degassing performance of cables are particularly important for the production of high-quality high-voltage cables. The co-cross-linking agent can quickly react with the polyethylene macromolecular chain free radicals produced by the hydrogen abstraction reaction. This reaction is faster than the cross-linking reaction of the polyethylene macromolecular chain growth and the generated polymer free radicals are stable, which can significantly reduce the amount of cross-linking agent added, thereby shortening the degassing time.
[0024] The bismaleimide structure contains active end groups and multiple double bond groups, which can play a role in cross-linking. However, bismaleimide has the problems of high brittleness and poor impact resistance, and its heat resistance in high-voltage cables needs to be improved. On the one hand, the applicant used 4-(4-hydroxyphenyl)phthalazine-1-ol and p-chloronitrobenzene with a naphthobiphenyl structure as raw materials, and synthesized a substance with a naphthobiphenyl and a diamine structure (product 2) under the action of an iron-based catalyst. The twisted and non-coplanar molecular structure of the naphthobiphenyl structure can destroy the regularity of the chain segment, reduce the crystallinity of bismaleimide, and improve the processability of the cross-linking agent. In addition, the rigid structure of the naphthobiphenyl structure also gives the cross-linking agent good heat resistance. On the other hand, The applicant mixed the product 2 with 2-(4-aminophenyl)-5-aminobenzimidazole containing a benzimidazole group and a diamine group, and further added maleic anhydride, cobalt acetate and acetic anhydride to synthesize bismaleimide containing a naphthalene biphenyl structure and bismaleimide containing a benzimidazole structure, i.e., a cross-linking agent. The benzimidazole ring is a rigid conjugated aromatic heterocycle, which can improve the heat resistance of the bismaleimide, and the proton donor NH bond of the imidazole ring can form an intermolecular hydrogen bond, increase the interchain force, and further improve the heat resistance and stability of the cross-linking agent. In addition, the cobalt ions and the iron ions in the catalyst and the imidazole groups can produce coordination interactions, enhance the stability of the cross-linking agent, and improve the service life of the cross-linking agent.
[0025] In some embodiments of the present invention, the antioxidant is any one of antioxidant 1010 , antioxidant 1076 and antioxidant 300 .
[0026] In some embodiments of the present invention, the method for preparing the modified styrene-maleic anhydride copolymer comprises the following steps:
[0027] 1) adding multi-walled carbon nanotubes to a mixed acid solution of sulfuric acid and nitric acid, heating to 70-80° C. and reflux for 5-6 hours, washing to pH=6.5-7.5, and drying to obtain acidified multi-walled carbon nanotubes for use;
[0028] 2) adding styrene and azobisisobutyronitrile to toluene, stirring to obtain a mixed solution for use, mixing maleic anhydride, the acidified multi-walled carbon nanotubes of step 1) and toluene, ultrasonicating, heating to 70-80° C., stirring for 30-40 min, dropping the mixed solution, stirring for 30-40 min, heating to 80-90° C., stirring for 50-70 min, cooling to room temperature, filtering, washing, and drying to obtain a reaction product for use;
[0029] 3) Take the reaction product of step 2), add erythritol, 1,8-diazabicyclo[5.4.0]undec-7-ene and DMF, heat to 110-130° C., stir for 23-25 hours, filter, wash and dry to obtain a modified styrene-maleic anhydride copolymer.
[0030] In some embodiments of the present invention, in step 2), the mass ratio of maleic anhydride, styrene and acidified multi-walled carbon nanotubes is 1:(1-1.2):(0.006-0.008).
[0031] Preferably, in step 2), the mass ratio of maleic anhydride, styrene and acidified multi-walled carbon nanotubes is 1:1.1:0.007.
[0032] In some embodiments of the present invention, in step 3), the mass ratio of the reaction product to erythritol is 1:(0.5-0.7).
[0033] Preferably, in step 3), the mass ratio of the reaction product to erythritol is 1:0.6.
[0034] Water tree refers to the branch-like local destruction phenomenon formed in a certain area of the insulation after a long period of time under the condition of relatively high electric field strength in a humid environment. That is, during the operation of the cable, the cross-linked polyethylene will degrade, which is called "water treeing". Water tree is an important reason for the aging and breakdown of cross-linked polyethylene cables, thereby reducing their service life. Therefore, the research and development of "anti-water tree" has become increasingly important.
[0035] On the one hand, the applicant selected maleic anhydride and styrene as raw materials to synthesize styrene-maleic anhydride copolymer. The styrene-maleic anhydride copolymer introduced polar groups, which improved the hydrophilicity of the polyethylene substrate and prevented the water in the insulating material from further condensing into water droplets. At the same time, the introduction of polar groups improved the breakdown strength of the composite material. Furthermore, the applicant grafted the styrene-maleic anhydride copolymer onto the surface of multiple carbon nanotubes, so that the modified styrene-maleic anhydride copolymer had a larger specific surface area, and the polarity and conductivity of the carbon nanotubes were conducive to further inhibiting the formation of water trees. On the other hand, the applicant grafted the styrene-maleic anhydride copolymer grafted with multiple carbon nanotubes with erythritol. The hydroxyl group in erythritol can undergo a cross-linking reaction with the acid anhydride to increase the hydrophilicity and stability of the styrene-maleic anhydride copolymer, thereby improving the anti-water tree performance. In addition, the structure of erythritol is added to the cross-linked polyethylene, which can improve the regularity of the polyethylene crystal nucleus, reduce the influence of space charge accumulation on the insulating material, and further improve the anti-water tree performance of the insulating material.
[0036] Another aspect of the present invention further provides a method for preparing the cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time as described in the above technical solution, comprising the following steps:
[0037] The low-density polyethylene, cross-linking agent, auxiliary cross-linking agent, antioxidant and modified styrene-maleic anhydride copolymer are stirred at 60-80°C for 0.1-1h and then kept warm for 13-16h to obtain a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The present invention uses low-density polyethylene as a main component, and then adds a cross-linking agent, a co-cross-linking agent, an antioxidant and a modified styrene-maleic anhydride copolymer to prepare a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time. Through the synergistic effect of the components, the cross-linked polyethylene insulation material has the advantages of ultra-short degassing time and excellent anti-water treeing properties.
[0040] (2) The present invention is based on a cross-linking agent containing a bismaleimide structure, introduces a naphthalene biphenyl structure, and forms a cross-linking agent with a bismaleimide containing a benzimidazole structure, thereby improving the heat resistance and stability of the bismaleimide, and making the insulating material have a shorter degassing time and higher quality.
[0041] (3) The present invention uses maleic anhydride and styrene as raw materials to synthesize styrene-maleic anhydride copolymer and grafts it with multi-walled carbon nanotubes, and then introduces erythritol, thereby improving the hydrophilicity and stability of cross-linked polyethylene and improving the anti-water tree performance of the insulating material.
[0042] (4) The cross-linked polyethylene insulation material prepared by the present invention has an ultra-short degassing time and excellent anti-water treeing properties, can be widely used in the field of cable insulation materials, and has good commercial application value. DETAILED DESCRIPTION
[0043] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0044] In the following examples and comparative examples, except for the co-crosslinking agent and the modified styrene-maleic anhydride copolymer, the other compound monomers and related reagents used can be purchased from the market. Among them, the density of the low-density polyethylene is 0.918 g / cm 3 , purchased from China Petrochemical Corporation; multi-walled carbon nanotubes were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; sulfuric acid and nitric acid were of analytical grade.
[0045] Preparation Example 1
[0046] The synthesis method of the co-crosslinking agent A comprises the following steps:
[0047] (1) 0.1 mol of 4-(4-hydroxyphenyl)phthalazin-1-ol and 0.2 mol of p-chloronitrobenzene were mixed, heated to 140° C., 3 g of potassium carbonate and 50 ml of DMF were added, and stirred for 30 min to obtain product 1 for later use;
[0048] (2) 8 g of Fe(NO3)3·9H2O was added to 40 ml of 1 wt% monobutyric acid aqueous solution, stirred for 15 min, 30 wt% ammonia water was added to adjust the pH to 6.3, stirred for 8 h, allowed to stand for 12 h, centrifuged, washed with deionized water 3 times, dried at 80°C for 12 h, 25 g of dicyandiamide was added, ground for 20 min, argon was introduced, the temperature was raised to 550°C, kept at this temperature for 3 h, then raised to 950°C, kept at this temperature for 4.5 h, cooled to room temperature, and the catalyst was obtained for use;
[0049] (3) Take 10 g of the product 1 of step (1), add 1.5 g of the catalyst of step (2) and 15 g of hydrazine hydrate, stir for 30 min, and obtain product 2 for later use;
[0050] (4) 10 g of the product 2 of step (3) and 8 g of 2-(4-aminophenyl)-5-aminobenzimidazole were mixed, 5 g of maleic anhydride and 50 ml of DMF were added, stirred for 30 min, condensed and refluxed for 3.5 h, filtered, washed with tetrahydrofuran and deionized water 3 times each, and dried at 60° C. for 12 h to obtain product 3 for use;
[0051] (5) 10 g of the product 3 of step (4), 10 ml of triethylamine and 100 ml of acetone were mixed, nitrogen was introduced, the temperature was raised to 60° C., 0.05 g of cobalt acetate and 20 ml of acetic anhydride were added, the mixture was stirred for 4 h, filtered, washed with tetrahydrofuran and deionized water 3 times each, and dried at 60° C. for 12 h to obtain a cross-linking agent A.
[0052] Preparation Example 2
[0053] The specific implementation manner of the cross-linking aid B is the same as that of the cross-linking aid A, except that in step (1), the molar number of p-chloronitrobenzene is replaced with 0.3 mol.
[0054] Preparation Example 3
[0055] The specific implementation manner of the cross-linking aid C is the same as that of the cross-linking aid A, except that in step (3), the mass of the catalyst is replaced with 0.5 g.
[0056] Preparation Example 4
[0057] The specific implementation manner of the cross-linking aid D is the same as that of the cross-linking aid A, except that in step (4), the mass of 2-(4-aminophenyl)-5-aminobenzimidazole is replaced with 6 g.
[0058] Preparation Example 5
[0059] The synthetic method of modified styrene-maleic anhydride copolymer A comprises the following steps:
[0060] 1) Add 0.3 g of multi-walled carbon nanotubes to a mixed acid solution of 150 ml of sulfuric acid and 50 ml of nitric acid, heat to 75° C. and reflux for 5.5 h, wash until pH = 7, and dry at 40° C. for 24 h to obtain acidified multi-walled carbon nanotubes for use;
[0061] 2) adding 11 g styrene and 0.02 g azobisisobutyronitrile to 40 ml toluene, stirring for 30 min to obtain a mixed solution for use, mixing 10 g maleic anhydride, 0.07 g acidified multi-walled carbon nanotubes obtained in step 1) and 200 ml toluene, ultrasonicating for 40 min, heating to 75° C. and stirring for 35 min, adding the mixed solution dropwise, stirring for 35 min, heating to 85° C., stirring for 60 min, cooling to room temperature, filtering, washing with toluene twice, and drying at 40° C. for 24 h to obtain a reaction product for use;
[0062] 3) Take 10 g of the reaction product of step 2), add 6 g of erythritol, 1.5 g of 1,8-diazabicyclo[5.4.0]undec-7-ene and 100 ml of DMF, heat to 120° C., stir for 24 h, filter, wash with ethyl acetate 3 times, and dry at 60° C. for 12 h to obtain modified styrene-maleic anhydride copolymer A.
[0063] Preparation Example 6
[0064] The specific implementation manner of the modified styrene-maleic anhydride copolymer B is the same as that of the modified styrene-maleic anhydride copolymer A, except that in step 2), the mass of styrene is replaced with 8 g.
[0065] Preparation Example 7
[0066] The specific implementation manner of the modified styrene-maleic anhydride copolymer C is the same as that of the modified styrene-maleic anhydride copolymer A, except that in step 2), the mass of the acidified multi-walled carbon nanotubes is replaced with 0.03 g.
[0067] Preparation Example 8
[0068] The specific implementation manner of the modified styrene-maleic anhydride copolymer D is the same as that of the modified styrene-maleic anhydride copolymer A, except that in step 3), the mass of erythritol is replaced with 3 g.
[0069] Example 1
[0070] A cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time comprises the following raw materials by weight: 95 parts of low-density polyethylene, 1.5 parts of dicumyl peroxide, 0.4 parts of a co-crosslinking agent A, 10104 parts of an antioxidant, and 7 parts of a modified styrene-maleic anhydride copolymer A.
[0071] The method for preparing the cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time in this embodiment comprises the following steps:
[0072] Low-density polyethylene, diisopropylbenzene peroxide, co-crosslinking agent A, antioxidant 1010 and modified styrene-maleic anhydride copolymer A were stirred at 70°C for 0.55h and then kept warm for 15h to obtain a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time.
[0073] Example 2
[0074] A cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time comprises the following raw materials by weight: 90 parts of low-density polyethylene, 1 part of dicumyl peroxide, 0.4 parts of auxiliary cross-linking agent A, 3002 parts of antioxidant, and 4 parts of modified styrene-maleic anhydride copolymer A.
[0075] The method for preparing the cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time in this embodiment comprises the following steps:
[0076] Low-density polyethylene, diisopropylbenzene peroxide, co-crosslinking agent A, antioxidant 300 and modified styrene-maleic anhydride copolymer A were stirred at 60°C for 1 hour and then kept warm for 16 hours to obtain a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time.
[0077] Example 3
[0078] A cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time comprises the following raw materials by weight: 100 parts of low-density polyethylene, 2 parts of dicumyl peroxide, 0.4 parts of auxiliary cross-linking agent A, 10766 parts of antioxidant and 10 parts of modified styrene-maleic anhydride copolymer A.
[0079] The method for preparing the cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time in this embodiment comprises the following steps:
[0080] Low-density polyethylene, diisopropylbenzene peroxide, co-crosslinking agent A, antioxidant 1076 and modified styrene-maleic anhydride copolymer A were stirred at 80°C for 0.1h and then kept warm for 13h to obtain a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time.
[0081] Example 4
[0082] A cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time comprises the following raw materials by weight: 92 parts of low-density polyethylene, 1.2 parts of dicumyl peroxide, 0.3 parts of a co-crosslinking agent A, 3003 parts of an antioxidant, and 7 parts of a modified styrene-maleic anhydride copolymer A.
[0083] The preparation method of the cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time in this embodiment is the same as that in Example 1.
[0084] Example 5
[0085] A cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time comprises the following raw materials by weight: 97 parts of low-density polyethylene, 1.8 parts of dicumyl peroxide, 0.5 parts of a co-crosslinking agent A, 10105 parts of an antioxidant, and 7 parts of a modified styrene-maleic anhydride copolymer A.
[0086] The preparation method of the cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time in this embodiment is the same as that in Example 1.
[0087] Example 6
[0088] This embodiment provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the cross-linking agent A is replaced by an equal amount of the cross-linking agent B.
[0089] Example 7
[0090] This embodiment provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the co-cross-linking agent A is replaced by an equal amount of the co-cross-linking agent C.
[0091] Example 8
[0092] This embodiment provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the cross-linking agent A is replaced by an equal amount of a cross-linking agent D.
[0093] Example 9
[0094] This embodiment provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified styrene-maleic anhydride copolymer A is replaced by an equal amount of modified styrene-maleic anhydride copolymer B.
[0095] Example 10
[0096] This embodiment provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified styrene-maleic anhydride copolymer A is replaced by an equal amount of modified styrene-maleic anhydride copolymer C.
[0097] Embodiment 11
[0098] This embodiment provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified styrene-maleic anhydride copolymer A is replaced by an equal amount of modified styrene-maleic anhydride copolymer D.
[0099] Example 12
[0100] This embodiment provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the cross-linking agent A is replaced by an equal amount of N,N-phenylene bismaleimide.
[0101] Comparative Example 1
[0102] This comparative example provides a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of styrene-maleic anhydride copolymer is used to replace the modified styrene-maleic anhydride copolymer A.
[0103] Styrene-maleic anhydride copolymer was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.
[0104] Performance Testing
[0105] The breakdown strength, degassing performance and water tree resistance of the cross-linked polyethylene insulation materials for ultra-high voltage cables with ultra-short degassing time of the above-mentioned Examples 1-12 and Comparative Example 1 were tested. The test results are shown in Table 1.
[0106] (1) Breakdown strength
[0107] The breakdown strength of the insulating materials obtained in Examples 1-12 and Comparative Example 1 was tested. Referring to GB / T 10437-2004, the greater the breakdown strength, the better the insulating electrical performance of the insulating material.
[0108] (2) Degassing performance
[0109] The by-product content of the insulating material of Examples 1-12 and Comparative Example 1 was tested by weight loss method. The test method is as follows: mg (5 g is used in the experiment, i.e. m is 5) of the sample is taken and sliced at 175°C using a flat vulcanizer to make it cross-linked. The slice making process is as follows: preheating for 30s, exhausting for 30s, pressurizing to 20MPa for 15min, cooling, placing in a 70°C blast oven for degassing for 2 hours, weighing its weight m1, and calculating:
[0110] Total cross-linked by-product content = (m-m1) / m×100%,
[0111] The lower the by-product content, the better the degassing performance of the cross-linked polyethylene insulation material is, which indirectly proves that it has a shorter degassing time.
[0112] (2) Water tree resistance
[0113] The insulating materials obtained in Examples 1-12 and Comparative Example 1 were subjected to accelerated water tree aging test, with reference to ASTM D6097a, where “ / ” means that no water tree growth was found by naked eyes.
[0114] Table 1
[0115]
[0116]
[0117] It can be seen from the data in Table 1 that the cross-linked polyethylene insulation materials in Examples 1-5 of the present invention have higher breakdown strength, better degassing performance and water tree resistance as a whole. Among them, Examples 6-8 respectively changed the addition ratio of p-chloronitrobenzene, catalyst and 2-(4-aminophenyl)-5-aminobenzimidazole in the auxiliary cross-linking agent, thereby showing the phenomenon of increased cross-linking by-products, decreased degassing performance and decreased breakdown strength, but had little effect on the water tree resistance; Examples 9-11 changed the use ratio of styrene, multi-carbon nanotubes and erythritol, the key components in the synthesis of modified styrene-maleic anhydride copolymer, resulting in decreased hydrophilicity and stability of the modified styrene-maleic anhydride copolymer, thereby resulting in the insulation material. The anti-water treeing performance and breakdown strength are reduced, but the amount of cross-linked by-products of the insulating material, i.e., the degassing performance, is not greatly affected; Example 12 uses conventional auxiliary cross-linking agent N,N-phenylene bismaleimide to replace auxiliary cross-linking agent A, and the test finds that the breakdown strength and degassing performance of the insulating material both show poor results, but have little effect on the anti-water treeing performance; Comparative Example 1 uses styrene-maleic anhydride copolymer to replace modified styrene-maleic anhydride copolymer A, and the test finds that the breakdown strength and anti-water treeing performance of the insulating material show poor results, but have little effect on the degassing performance.
[0118] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time, characterized in that: The cross-linked polyethylene insulation material comprises the following raw materials in parts by weight: 90-100 parts of low-density polyethylene, 1-2 parts of a cross-linking agent, 0.3-0.5 parts of a co-cross-linking agent, 2-6 parts of an antioxidant, and 4-10 parts of a modified styrene-maleic anhydride copolymer; The preparation method of the cross-linking aid comprises the following steps: (1) 4-(4-hydroxyphenyl)phthalazin-1-ol and p-chloronitrobenzene are mixed, heated to 135-145° C., potassium carbonate and DMF are added, and stirred to obtain product 1 for later use; (2) Add Fe(NO3)3·9H2O to the monobutyric acid aqueous solution, stir, add ammonia water to adjust the pH to 6-6.5, stir, let stand, centrifuge, wash, dry, add dicyandiamide, grind, introduce inert gas, heat to 500-600°C, keep warm for 2-4h, then heat to 900-1000°C, keep warm for 4-5h, cool to room temperature, and obtain the catalyst for use; (3) taking the product 1 of step (1), adding the catalyst and hydrazine hydrate of step (2), stirring, and obtaining the product 2 for later use; (4) Mix the product 2 of step (3) and 2-(4-aminophenyl)-5-aminobenzimidazole, add maleic anhydride and DMF, stir, condense and reflux for 3-4 hours, filter, wash, and dry to obtain product 3 for use; (5) The product 3 of step (4), triethylamine and acetone are mixed, an inert gas is introduced, the temperature is raised to 55-65° C., cobalt acetate and acetic anhydride are added, the mixture is stirred, filtered, washed and dried to obtain a cross-linking agent; In the step (1), the molar ratio of 4-(4-hydroxyphenyl)phthalazin-1-ol to p-chloronitrobenzene is 1:(2-2.1); In the step (4), the mass ratio of the product 2 to 2-(4-aminophenyl)-5-aminobenzimidazole is 1:(0.7-0.9); The preparation method of the modified styrene-maleic anhydride copolymer comprises the following steps: 1) Add multi-walled carbon nanotubes to a mixed acid solution of sulfuric acid and nitric acid, heat to 70-80°C and reflux for 5-6 hours, wash to pH = 6.5-7.5, and dry to obtain acidified multi-walled carbon nanotubes for use; 2) Add styrene and azobisisobutyronitrile to toluene, stir to obtain a mixed solution for use, mix maleic anhydride, the acidified multi-walled carbon nanotubes of step 1) and toluene, ultrasonicate, heat to 70-80°C, stir for 30-40min, dropwise add the mixed solution, stir for 30-40min, heat to 80-90°C, stir for 50-70min, cool to room temperature, filter, wash, and dry to obtain a reaction product for use; 3) taking the reaction product of step 2), adding erythritol, 1,8-diazabicyclo[5.4.0]undec-7-ene and DMF, heating to 110-130° C., stirring for 23-25 hours, filtering, washing and drying to obtain a modified styrene-maleic anhydride copolymer; In the step 2), the mass ratio of maleic anhydride, styrene and acidified multi-walled carbon nanotubes is 1:(1-1.2):(0.006-0.008); In the step 3), the mass ratio of the reaction product to erythritol is 1:(0.5-0.7).
2. The cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time according to claim 1, characterized in that: The density of the low-density polyethylene is 0.915-0.930 g / cm 3 .
3. The cross-linked polyethylene insulation material for ultra-high voltage cables with ultra-short degassing time according to claim 1, characterized in that: The cross-linking agent is dicumyl peroxide.
4. A method for preparing a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: The low-density polyethylene, cross-linking agent, auxiliary cross-linking agent, antioxidant and modified styrene-maleic anhydride copolymer are stirred at 60-80°C for 0.1-1h and then kept warm for 13-16h to obtain a cross-linked polyethylene insulation material for ultra-high voltage cables with an ultra-short degassing time.
Citation Information
Patent Citations
High-voltage direct-current cable insulation material and preparation method thereof
CN108623877A
Resin composition, power cable, and method for manufacturing power cable
CN116601234A